MOTIVASI MASYARAKAT DALAM PEMANFAATAN TANAMAN OBAT KELUARGA (TOGA) UNTUK PENINGKATAN DERAJAT KESEHATAN DI DESA BUNDER KECAMATAN PADEMAWU KABUPATEB PAMEKASNAN - RAHMAN, HILMAH NOVIANDRY (Jurnal Sains dan Teknologi Kesehatan, 2024)
Introduction : Indonesia is a country that has a tropical climate, has very abundant biodiversity, including spices. Family medicinal plants are more often used as a community choice as a treatment because they are considered safer without side effects, cheap and easy to obtain. The purpose of this study was to find out about community motivation in the use offamily medicinal plants to improve health status in Bunder Village, Pademawu District, Pamekasan Regency. Methods : The design used in this research is descriptive. The population and sample in this study were people who used and grew family medicinal plants in Bunder Village as many as 20 people. With Sampling technique total sampling. The instrument used is a closed ended type dichotomy question with a Likert scale measurement. The results of the study were processed through Editing, Coding, Scoring, Tabulating and analyzed descriptively the percentages presented in the form of tables and narratives. Result: almost all (95%) respondents have high motivation in using Family Medicinal Plants (TOGA) to improve health status and none (0%) respondents have low motivation in using Family Medicinal Plants (TOGA) to improve health status. Conclusion : It is hoped that the Bunder Village Community can maintain their behavior in using Family Medicinal Plants and can motivate others around them to use Family Medicinal Plants. Keywords: Family medicinal plants, Community motivation, Health degree